Boiler Operator's Guide, 5E - Kohan, Anthony L.; Wohlfarth, Ray (McGraw-Hill Education, 2021)
This book has been widely used by boiler personnel all over the world. From the classroom to the control room of any plant, it is an excellent reference for the boiler industry. This fifth edition has been revised to include requirements of the latest codes of the American Society of Mechanical Engineers, the National Board of Boiler and Pressure Vessel Inspectors, and other national professional organizations. In addition, recent technological developments in the boiler industry have been included. Among the boilers with new technology are condensing boilers, hybrid boilers, solar heating boilers, and solar power generation boilers.